Low birth weight and its relation to physical fitness parameters in children: Its negative effect on muscle strength and cardiorespiratory endurance. Issue 1 (12th March 2021) - de Souza, Livia Victorino; de Meneck, Franciele; Parizotto, Giovanna Pachele; Franco, Maria
Abstract: Background: There is increasing evidence that low birth weight has a negative effect on physical fitness, muscle strength, and cardiorespiratory endurance, although the findings are inconsistent. Objectives: This study aimed to evaluate whether birth weight acts as a prenatal determinant of physical fitness parameters and to determine the role of environmental or biological variables on this effect. Methods: One hundred and sixty‐seven children aged 6–14 years were included in this study. The anthropometric data, physical activity index, standing long jump, flexibility, handgrip strength, and cardiorespiratory fitness were evaluated. Results: A positive correlation was found between birth weight and cardiorespiratory fitness ( r =  .349; p <  .001), right handgrip strength ( r =  .337; p <  .001), and left handgrip strength (r =  .320; p <  .001), suggesting that children with low birth weight had the worst performance in both cardiorespiratory endurance and grip strength tests. These findings remained significant after adjustment for prematurity, sex, age, physical activity index, and body mass index (BMI). Stepwise multiple regression analyses revealed a significant interaction of high birth weight, older age, and low BMI in predicting better cardiorespiratory endurance ( R 2  = .308). When handgrip strength was tested as the dependent variable, we found that high birth weight, male sex, and older age emerged as important determinants for both sides. Conclusion: Children aged 6–14 years born with a birth weight < 2.5 kg have low handgrip strength and cardiorespiratory fitness, which seems to be mediated partially by influences of both prenatal environment (e.g., birth weight) and biological variables (e.g., age, sex, BMI).